Self, Body, and Relation: a Study of FTM Transgender in Jakarta - Sri Agustine; Evi Lina Sutrisno; Dewi Candraningrum (Yayasan Jurnal Perempuan, 2015)
The existence of Male to Female (MTF) or in Indonesian word known as Waria is more popular than Female to Male (FTM). Existence of FTM or someone biologically born as woman but identified herself as man is not well-researched and well-documented. That is why this group is difficult to be identified in the public discourse. Jakarta was chosen in this research as this city represented FTM from other areas around Indonesia. This study found that someone that biologically woman is not otomatically identified herself as woman. The process of self-definition is fluid. In the process of finding the self, FTM faced violences from states, society, work-place, and family.